Balanced Scorecard: Literature Review and Implementation in Organization - Deni Ahmad Taufik; Humiras Hardi Purba; Hasbullah Hasbullah (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
The balanced scorecard is a formal management technique for developing, implementing, and managing business strategies. It isn't easy to ascertain the technique's success. Most of the literature on its implementation is put out by those with a vested interest in its success as a commercial product. Much has been written about barriers to strategy implementation but not specifically to implementing a balanced scorecard. The literature review in this paper shows that studies on BSC implementation in corporate organizations focus on improving organizational performance, assisting in decision making, assisting in component selection, evaluating production and learning and sustainable growth. This paper provides benefits for further research to add to the literature and understanding of the implementation of the Balanced Scorecard in any organization.